Study of coupling configurations of capacitive power transfer system with four metal plates. Issue 2 (15th September 2019) - Zhu, Qi; Zang, Shaoge; Zou, Lixiang Jackie; Zhang, Guanguan; Su, Mei; Hu, Aiguo Patrick
Abstract: In this paper, possible coupling configurations of a four-plate capacitive power transfer system are studied by varying the combinations of its input and output ports. A voltage source is applied between two of the four plates, and a load is connected to the other two to form different circuit topologies. A mathematical model based on a 4 × 4 mutual capacitance matrix is established for equidistantly placed four identical metal plates. Based on the proposed model, four separate circuit topologies are identified and analysed in detail and described in a general form. The electric field distributions of the coupling configurations are simulated by ANSYS Maxwell. The theoretical modeling and analysis are then verified by a practical system, in which four aluminum plates of 300 mm × 300 mm are used and placed with a gap of 10 mm between adjacent plates. The experimental results show that the measured output voltage and power under the four coupling configurations are in good agreement with the theoretical results. It has found that the voltage gain is the highest when the two inner plates are connected to the source, and this coupling configuration also has the lowest leakage electric field.